The Effect Of Thin Capitalization, Capital Intensity On Tax Avoidance With Institutional Ownership Moderating Variable - Kurniawati, Dewi; Aloysius Harry Mukti (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The Effect of Thin Capitalization, Capital Intensity on Tax Avoidance with Institutional Ownership Variables (Empirical Study on Property, Real Estate, and Infrastructure Companies listed on the Indonesia Stock Exchange in 2018-2020). This study aims to examine the effect of thin capitalization, capital intensity on tax avoidance with institutional ownership variables. The population in this study are all property, real estate, and infrastructure sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used is the Non-Probability Sampling method and obtained as many as 117 data samples. The analytical method used is Multiple Linear Regression. The results show that Thin Capitalization has a positive effect on tax avoidance, Capital Intensity has a positive effect on tax avoidance.